Penerapan Teori Laissez Faire Dalam Penyutradaraan Video Feature: ”Berani Melangkah Menuju Sejahtera” - Artikha Ruth Sinaga; Herlina Agustin; Retasari Dewi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Feature video "Berani Melangkah Menuju Sejahtera” is a final project that raises the issue of student mental health and aims to increase the utilization of counseling services Pusat Penguatan Karakter dan Konseling (P2K2) at Padjadjaran University. In the making process, the writer acts as a director who is responsible for the entire creative process by applying the Laissez Faire theory in directing. The purpose of writing this report is to explain the director's duties and the application of Laissez Faire theory. The creation methods applied are pre-production, production, and post-production processes. The results show that the application of Laissez Faire theory is effective in giving freedom to actors to express naturally, so as to build audience empathy for the issues raised. In conclusion, in the video feature “Berani Melangkah Menuju Sejahtera” with the application of Laissez Faire theory for the director is very important to create a strong and authentic message, so that it can increase students' awareness to dare to seek professional help to achieve psychological well-being.